Translation Method Analysis on Figurative Language in Novel Crazy Rich Asians Translated into Kaya Tujuh Turunan - Riris Mutiara Simamora; Andre Priyono (Badan Pengembangan dan Pembinaan Bahasa, 2022)
This research is aimed to find the types of figurative language used and to identify translation method that the translator chooses to translate figurative language from Crazy Rich Asians novel into Kaya Tujuh Turunan. This research is descriptive qualitative research with secondary data. The object of this research is a novel by Kevin Kwan titled Crazy Rich Asians (2013) which translated into Kaya Tujuh Turunan (2016) by Cindy Kristianto. The novel is analyzed using Abram’s figurative language theory (1999) and Newmark’s translation method. The novel contains 154 figurative languages. After examining the figurative language data in Crazy Rich Asians, it was discovered that there were 51 similes, 43 hyperboles, 25 imagery, 22 metonymy, and 13 ironies. According to the findings of the research, six of the eight translation methods given by Newmark were employed in translating the words, phrases, clauses, and sentences from English to Indonesian in the novel Crazy Rich Asians. They are literal (94), faithful (4), semantic (3), idiomatic (2), and communicative translation (21). According to the findings of the analysis, the most dominant translation method utilized in translating the novel is literal translation. Based on the most often employed translation methods in translating the novel, it is possible to deduce that the translator prioritizes the corresponding word or expression in the target language that has the same meaning and nuance as in the source language. AbstrakPenelitian ini bertujuan untuk mengidentifikasi tipe gaya bahasa kiasan dan metode penerjemahan gaya bahasa dari novel Crazy Rich Asians menjadi Kaya Tujuh Turunan. Penelitian ini merupakan penelitian yang berbentuk deskriptif kualitatif dengan menggunakan data sekunder. Objek dalam penelitian ini adalah novel karya Kevin Kwan yang berjudul Crazy Rich Asians (2013) dengan membandingkan versi terjemahan Bahasa Indonesia Kaya Tujuh Turunan (2016) karya Cindy Kristianto. Novel ini dianalisis dengan menggunakan teori Bahasa kiasan dari Abram (1999) dan metode terjemahan Newmark. Setelah melakukan analisis, ditemukan 154 gaya bahasa kiasan, yaitu 51 bentuk simile, 43 bentuk hiperbola, 25 bentuk imagery, 22 bentuk metonimi, dan 13 bentuk ironi. Ditemukan enam metode dalam penerjemahan gaya bahasa kiasan, yaitu terjemahan literal (94), terjemahan setia (4), terjemahan semantik (3), terjemahan idiomatik (2), dan terjemahan komunikatif (21). Hasil penelitian ini menyimpulkan bahwa metode penerjemahan yang paling dominan adalah terjemahan literal. Metode ini dipakai penerjemah untuk memprioritaskan ekspresi yang paling sesuai dan berterima dalam Bahasa sasaran sehingga pesan dan nuansa yang disampaikan sama seperti dalam Bahasa sumber.